The Effect Of Liquidity And Solvability On Financial Performance At Pt. Matahari Department Store, Tbk - Rika Apriansyah; Iskandar Iskandar; Hayani Hayani (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
The purpose of this study was to determine the effect of Liquidity and Solvency on Financial Performance at PT. Matahari Departement Store, Tbk. The results of the study showed that (1) Liquidity has a partial significant effect on Financial Performance, as evidenced by the Liquidity variable's significance value being lower than the real level (0.006 <0.05), meaning that the Liquidity variable has a significant effect on Financial Performance. (2) Solvency has a partial significant effect on Financial Performance, as evidenced by the Solvency variable's significance value being lower than the real level (0.005 <0.05), meaning that the Solvency variable has a significant effect on Financial Performance. (3) Liquidity and Solvency have a simultaneous significant effect on Financial Performance at PT. Matahari Departement Store, Tbk. This can be seen from the significance value being lower than the real level (0.000 <0.05), meaning that the Liquidity (X1) and Solvency (X2) variables together have a significant effect on Financial Performance.